Scientific aspects of the personality of Imam Sahnun (Journal of Human Sciences, 2022)
The study actuly hed light on gclentif aspects of imamate ,abusaid abdelsam ben said ben habeb altakoukhythe great imamateof marocco who is  called “sahnon “ and who wrote trie “greatcorpus “ , and is one the fullowcrs of imamate “malik “,  and who spre ad that believe in “240 h “ he have study under famous scholars like ben abi kharija , bahlol ,ali ben ziad ,ben hassan , ben ashras , and khanem. He followed their schooi and become as one of them , he was so famous in morocco , and he teached many greduntss until he died in year “one hundred and eighty seven “ he was very keen when supervised judgeship he was succecded by his son ,and sback ben khalil , saed ben nemer, and abdulla ben ghafek  , mohamed ben abdulla ben abdoss , wahab ben nafie and many other scholar of jursiprudance ,and he was so famous thnt few of scholars rechead his prestnge.